2023
DOI: 10.1007/s00442-023-05447-1
|View full text |Cite
|
Sign up to set email alerts
|

Tree species identity, canopy structure and prey availability differentially affect canopy spider diversity and trophic composition

Benjamin Wildermuth,
Clemens Dönges,
Dragan Matevski
et al.

Abstract: Forest canopies maintain a high proportion of arthropod diversity. The drivers that structure these communities, however, are poorly understood. Therefore, integrative research connecting tree species identity and environmental stand properties with taxonomic and functional community composition of canopy arthropods is required. In this study, we investigated how the taxonomic, functional and trophic composition of arboreal spider communities is affected by tree species composition and associated differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 75 publications
(132 reference statements)
1
3
0
Order By: Relevance
“…This supports the finding of Roques et al (2006) who reported that in Europe mostly polyphagous arthropods feed on nonnative Douglas fir. Notably, arthropod communities in monospecific conifer stands were promoted by canopy openness, corroborating that stand structural properties are major drivers of arthropod communities in coniferous forests (Kriegel et al, 2021;Wildermuth, Dönges, et al, 2023). This positive effect of openness in conifers on taxon richness and the abovereported negative effect of lacking microhabitats in Douglas fir on taxon richness support our fourth hypothesis that structural habitat conditions imposed by the tree species contribute to explaining observed diversity patterns.…”
Section: Mixture Effects and Community Compositionsupporting
confidence: 77%
See 2 more Smart Citations
“…This supports the finding of Roques et al (2006) who reported that in Europe mostly polyphagous arthropods feed on nonnative Douglas fir. Notably, arthropod communities in monospecific conifer stands were promoted by canopy openness, corroborating that stand structural properties are major drivers of arthropod communities in coniferous forests (Kriegel et al, 2021;Wildermuth, Dönges, et al, 2023). This positive effect of openness in conifers on taxon richness and the abovereported negative effect of lacking microhabitats in Douglas fir on taxon richness support our fourth hypothesis that structural habitat conditions imposed by the tree species contribute to explaining observed diversity patterns.…”
Section: Mixture Effects and Community Compositionsupporting
confidence: 77%
“…A possible explanation for the lack of such an effect in our study might be that the isolation effects of trees in admixture with phylogenetically distant tree species reduce the number of associated specialist arthropods (Gossner et al, 2009; Seifert et al, 2020; Yguel et al, 2011). We conclude that broadleaf–conifer mixtures do not necessarily promote associated diversity, but can buffer negative tree‐species identity effects of economically attractive (non‐native) conifers (Budde et al, 2011; Leidinger et al, 2021; Wildermuth, Dönges, et al, 2023). A recent study, however, showed that, over a 14 year‐timespan, ground beetle diversity was increasing in temperate broadleaf–conifer mixtures, but decreasing in coniferous monocultures, indicating the positive long‐term effects of such mixtures (Evans et al, 2022).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This flexibility also allows the MLS user to approach and circumnavigate areas of dense vegetation or other complex structures, avoiding occlusion by tree stems or large shrubs and thus overcoming a limitation of TLS (Abegg et al, 2017) to obtain highly detailed scans of all objects. Researchers have recently taken advantage of MLS's flexibility to investigate seasonality in forest structural complexity (Neudam et al, 2022), quantify crown defoliation and tree vitality (Heidenreich & Seidel, 2022), and study the effects of canopy structure on canopy spider diversity (Wildermuth et al, 2023).…”
mentioning
confidence: 99%